SITUATIONAL ANALYSIS OF THE IMPACT OF GLOBALIZATION ON CULTURAL HERITAGE PRESERVATION - Anufrieva, Natalya; Kamyanets, Alexander; Scherbakova, Anna; Kuznetsova1, Elena; Zanina, Kseniya (Revista Inclusiones, 2020)
The article deals with the potential of situational analysis in studying the issues of cultural heritage preservation that allows one to identify both negative and positive consequences in the solutions to these problems. The authors name the most significant situations of social interaction of subjects that are connected to cultural heritage: the situation of consent, the situation of confrontation, the situation of partnership and the situation of coexistence. The authors present the results of the study of this topic according to these situations. The authors outline the prospects for using the positive potential of globalization in the preservation of cultural heritage as well as the organizational conditions of this process. Particular attention is paid to the opportunities to transition from one social interaction situation to another within the framework of a single cycle of occurring destruction or cultural heritage preservation in the context of globalization. The analysis presented in the article can be of interest to a wide range of specialists and researchers associated with cultural heritage preservation. For researchers and various specialists, the authors put forward a comprehensive outlook on the problems of cultural heritage thanks to the interactionist approach that considers the interests of all parties invested in solving these problems.